New design of a tapered bored pile For installation in structurally unstable soils - Samorodov, Oleksandr; Ubyivovk, Artem; Kupreichyk, Anna; Naydenova, Victoria (Academic journal Industrial Machine Building Civil Engineering, 2018)
New designs of bored piles with a tapered shaft shape are proposed. To confirm reduction or absence of the potential impact of additional load (negative) friction forces effectiveness on piles lateral surfaces in structurally unstable soils (fill-up grounds etc.) due to a change in the edge slope angle, laboratory experimental research on models of tapered piles have been conducted; the confirming results have been provided and described in detail in the laboratory experimental research. The impact of the changed slope angle of the edge on the effect of additional load friction forces on the lateral surfaces of experimental piles was demonstrated; the correlation between the change in taper of piles and the decrease in their surface area has been proven.
Keywords: tapered pile; soil subsidence; lateral surface; additional load friction forces